Mapeamento geomorfológico e zoneamento ambiental de fragilidades na bacia hidrográfica do Rio Barra Seca, Espírito Santo - Schineider, Vailson (2011)
A growing role of geomorphology as a discipline integrating earth science approaches to the environmental nature, focusing on land use in rural and urban societies. In this sense, the purpose of this work focuses on two main goals: the making of the geomorphological map at a scale of 1:100,000 for the River Basin Barra Seca, located in the north / northwest of the State of the Espírito Santo, as a contribution to the fundamental bases for the physical removal in the State, in view of the vacuum work aimed at this issue and limiting the scale RADAMBRASIL for more detailed work. Secondly, based on local geomorphology an environmental zoning of fragility to erosion, analyzing the strengths and limitations of natural subspaces of the basin, applying it to the methodology of empirical analysis of fragility of the relief proposed by Ross (1994). The methods chosen for conducting the research proved advantageous for providing flexibility as to the results, are easy to understand and implement, and efficient, by presenting results commensurate with the scale and the reality found in the study area.